Model Asistensi Pelaporan eSPT Bagi Wajib Pajak Orang Pribadi Sebagai Upaya Peningkatan Kepatuhan Pajak Di KPP Pratama Bekasi Barat - Sumarno Manrejo; Tri Yulaeli (Perbanas Institute, 2022)
This community service activity program is a form of collaboration between Bhayagkara University Jakarta and the West Bekasi Pratama Tax Service Office in the form of an assistance model for individual taxpayers who will carry out their tax obligations, especially reporting eSPT for the 2021 fiscal year. The place for implementing Abdimas is centered at the Tax Service Office. Pratama Bekasi Barat and several other locations such as sub-districts and urban villages in the Bekasi area. The applied assistance model is expected to provide direct solutions to taxpayers, both in terms of technical calculations, filling and reporting of eSPT. The results of the eSPT reporting assistance model for individual taxpayers for the 2021 fiscal year are very beneficial for both the taxpayers themselves because they can help solve their tax problems directly and the West Bekasi Tax Service Office, because they can help reduce their workload and at the same time help deal with problems. taxpayers so that tax compliance will increase. Taxpayers, armed with the experience gained, are expected to be able to carry out their tax rights and obligations independently in the next tax year in accordance with the mandate of implementing the self-assessment system. Tax volunteer participants in addition to getting direct experience in the field can also claim to be part of the Merdeka Learning Campus Merdeka (MBKM) form, this is in line with the current policy of the Ministry of Education and Culture of the Republic of Indonesia.